Gender differences in climate change denial in Sweden: the role of threatened masculinity - Remsö, Amanda; Bäck, Hanna; Aurora Renström, Emma (Frontiers in Psychology, 2024)
Previous research in the Western world shows that men are in general more likely than women to deny human-induced climate change or certain aspects of it. We hypothesize that threatened masculinity contributes to such gender differences in Sweden. Threatened masculinity refers to the perception that a man’s masculinity is being challenged, undermined, or devalued, often due to societal changes that advance women’s rights. Given that environmental care and concern are typically associated with femininity, men who perceive that masculinity is threatened may be more likely to deny climate change to restore a sense of masculinity. Across three cross-sectional online surveys with representative samples of Swedish adults (total N = 2,476), men were more likely to deny climate change than women. Threatened masculinity—measured by belief in a shift in sexism and belongingness with men’s rights activists—predicted climate change denial. In line with our hypothesis, belief in a sexism shift and, to a lesser extent, belongingness with men’s rights activists mediated from gender to climate change denial. Hence threatened masculinity contributes to a higher tendency among men compared to women to deny climate change in these samples. This research adds to the understanding of gender gaps in environmental attitudes found in many Western countries and highlights climate change denial as a potential correlate of the growing gender-related polarization observed in these contexts.